THE EFFECT OF SERVICE QUALITY ON REPURCHASE INTEREST IN HOME CLEANER SERVICES THROUGH CUSTOMER SATISFACTION AS AN INTERVENING VARIABLE - Ginting, Ninda; Rini, Endang Sulistya; Sembiring, Beby Karina Fawzeea (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
Cleaning service is a service provided to the hygiene of a building carried out carefully and thoroughly with the help of mechanical and non-machine hygiene tools, as well as chemical (chemical) performed by a sanitary officer. (cleaner). Many people don't have the time or energy to clean their own homes or workplaces so that's where the need for cleaning services arises. The aim of this study is to analyze the influence of quality of service on interest in re-purchase of home cleaner services through consumer satisfaction as an intervening variable. The type of research used in this study is explanatory research with a quantitative approach, which is a method of research intended to explain the position of the variables studied and the influence between one variable and another variable as well as to test the hypotheses that have been formulated. The results of the research were that the quality of service had a positive and significant influence on the interest in re-purchase in SAS Home Cleaner Field. It shows that the better the quality of the service performed, the greater the interest in re-purchase